Abstrak Tulisan ini menguraikan tentang evaluasi data agroklimat klasifikasi Schmid-Ferguson di Pulau Lombok berdasarkan data-data curah hujan terbaru. Metode yang digunakan adalah interpolasi atau ektrapolasi dengan aplikasi SIG. Hasil penelitian menunju - Gunawan, Erin Ryantin (Jurnal PIJAR, 2008)
Abstract: Wax esters were obtained from lipase-catalysed alcoholysis of palm oil fractions and oleyl alcohol, using n-hexane as solvent. The percent yield of wax esters synthesized from palm oil, palm olein and palm stearin at the optimum condition were 80,7%, 80%, 78,7%, respectively. And the percent yield of wax esters synthesized from palm kernel oil, palm kernel olein and palm kernel stearin were 84,4%, 82,9%, 88,6%, respectively. The saponification value of palm oil, stearin and olein esters are lower than palm kernel oil, stearin and olein esters. The average of the iodine value of esters from palm oil fraction is higher compared with commercial esters. The solubility of wax esters from all sources increased from C1 to C6 of alcohol. Compared with viscosity of commercial ester, wax esters have low viscosity. Similar result for measured of the acid value.Key words: Wax ester, Lipase-catalysed, palm oil fraction, saponification value